The α-synuclein gene in multiple system atrophy. Issue 4 (16th March 2006) - Ozawa, T; Healy, D G; Abou-Sleiman, P M; Ahmadi, K R; Quinn, N; Lees, A J; Shaw, K; Wullner, U; Berciano, J; Moller, J C; Kamm, C; Burk, K; et al.
Abstract : Background: The formation of α-synuclein aggregates may be a critical event in the pathogenesis of multiple system atrophy (MSA). However, the role of this gene in the aetiology of MSA is unknown and untested. Method: The linkage disequilibrium (LD) structure of the α-synuclein gene was established and LD patterns were used to identify a set of tagging single nucleotide polymorphisms (SNPs) that represent 95% of the haplotype diversity across the entire gene. The effect of polymorphisms on the pathological expression of MSA in pathologically confirmed cases was also evaluated. Results and conclusion: In 253 Gilman probable or definite MSA patients, 457 possible, probable, and definite MSA cases and 1472 controls, a frequency difference for the individual tagging SNPs or tag-defined haplotypes was not detected. No effect was observed of polymorphisms on the pathological expression of MSA in pathologically confirmed cases.